Sebatian perisa dalam minyak halia (Zingiber officinale) dan lengkuas (Languas galanga)-(Flavour components in ginger and galanga oil) - Omar, Muhammad Nor (Malaysian Agricultural Research and Development Institute (MARDI), 1991)

(untitled)
Volatile oils of ginger (Zingiber officinale) and galanga (Languas galanga) were extracted from fresh and dried rhizomes using normal and vacuum steam distillation. Distillates were continuously extracted with dichloromcthane. Flavour compounds of the extracted volatile oil of ginger and galanga have been identified using gas chromatography, Kovats retention indices, odour evaluation and gas chromatography-mass spectrometry analysis. Thirteen aroma components were identified in ginger oil and fifteen components in galanga oil.